PRODUKTIVITAS TANAMAN CABAI MERAH BESAR PADA BERBAGAI DOSIS PUPUK KANDANG DAN JARAK TANAM - MAMMA, SARAWA; RAHNI, NINI MILA; ALAM, SYAMSU (Jurnal Agroteknos, 2024)
Large red chilies are a horticultural commodity that has quite high economic in Indonesia. This research aims to determine the effect of cow manure and planting distance on the production of large chili plants. The research was carried out at the Experimental Fields 2 of Agricultural Faculties of Halu Oleo University from November 2022 to April 2023. The experimental design used was a randomized block design in a factorial pattern consisting of 2 factor. The firs factors is cow manure which consists of 4 doses, namely without manure (Ko), 7,5 t/ha (K1), 15 t /ha (K2), and 22,5 t/ha (K3). The second factors is plant distance which consist of 3 types, namely plant distance 30 cm x 30 cm (J1), 30 cm x 40 cm (J2), and 30 cm x 50 cm (J3). Each treatment was repeated 3 times so that there were 36 experimental unit. The variables observed were the number of branches, number of flowers, length of fruit, number of fruit and weight of fruit. The results of the research showed that there was an interaction effect between the manure application treatment and plant spacing treatment on the production of large chili plant. The treatment of providing 15 t/ha of manure with a planting distance of 30 cm x 40 cm (J2K2) gives the highest production of large red chilies, namely 16,39 t/ha.